Transcriptional inhibition by CDK7/9 inhibitor SNS-032 abrogates oncogene addiction and reduces liver metastasis in uveal melanoma - Jing Zhang; Shenglan Liu; Qianyun Ye; Jingxuan Pan (Molecular Cancer, 2019)
Abstract Background Life of patients with uveal melanoma (UM) is largely threatened by liver metastasis. Little is known about the drivers of liver organotropic metastasis in UM. The elevated activity of transcription of oncogenes is presumably to drive aspects of tumors. We hypothesized that inhibition of transcription by cyclin-dependent kinase 7/9 (CDK7/9) inhibitor SNS-032 diminished liver metastasis by abrogating the putative oncogenes in charge of colonization, stemness, cell motility of UM cells in host liver microenvironment. Methods The effects of SNS-032 on the expression of the relevant oncogenes were examined by qRT-PCR and Western blotting analysis. Proliferative activity, frequency of CSCs and liver metastasis were evaluated by using NOD-SCID mouse xenograft model and NOG mouse model, respectively. Results The results showed that CDK7/9 were highly expressed in UM cells, and SNS-032 significantly suppressed the cellular proliferation, induced apoptosis, and inhibited the outgrowth of xenografted UM cells and PDX tumors in NOD-SCID mice, repressed the cancer stem-like cell (CSC) properties through transcriptional inhibition of stemness-related protein Krüppel-like factor 4 (KLF4), inhibited the invasive phonotypes of UM cells through matrix metalloproteinase 9 (MMP9). Mechanistically, SNS-032 repressed the c-Myc-dependent transcription of RhoA gene, and thereby lowered the RhoA GTPase activity and actin polymerization, and subsequently inhibited cell motility and liver metastasis. Conclusions In conclusion, we validate a set of transcription factors which confer metastatic traits (e.g., KLF4 for CSCs, c-Myc for cell motility) in UM cells. Our results identify SNS-032 as a promising therapeutic agent, and warrant a clinical trial in patients with metastatic UM.